Đặc điểm kinh doanh Homestay du lịch cộng đồng và hàm ý chính sách giảm nghèo: Bằng chứng từ mô hình Heckman, kỹ thuật Lasso và thang đo Likert - Đỗ Xuân , Luận (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This article aims to analyze the characteristics of homestay businesses and propose policy interventions to reduce poverty through community-based tourism development. Based on data collected from interviews with 370 community-based tourism households in Northwestern Vietnam and employing the Heckman regression model, the Lasso technique, and the Likert scale, the results showed that homestay business particularly belongs to higher classes. Homestay owners or their relatives and friends often work in the local government. Homestay owners also have better access to banking and financial services than others. Indigenous peoples are constrained to operating homestay businesses due to resource barriers such as lack of capital, knowledge, and social relationships. The role of tourism associations and cooperatives in enhancing people’s participation and benefits from homestay is still limited. While communities actively contribute to the conservation and development of indigenous cultural and natural resources, the development of individual homestay may suffer unsustainability. The government should therefore support the community in developing tourism associations, establishing cooperatives, and enhancing access to banking services and business knowledge.